PENGARUH EVENT TERHADAP REVISIT INTENTION DENGAN DESTINATION IMAGE DAN CUSTOMER EXPERIENCE SEBAGAI VARIABEL INTERVENING (Studi Pada Event Gawai Dayak Kota Pontianak) - Yohanes, Yohanes Gunawan (Jurnal Manajemen Update, 2018)
This research aims to examine and analyze the effect of events on the destination image and customer experience as well as their impact on the revisit intention at Gawai Dayak event in Pontianak city. This research is causal research using a quantitative approach. The population are all people who visited the Gawai Dayak event. The sampling technique used is non-probability sampling technique in the form of purposive sampling method. The total sample of 100 respondents. The data analysis method used is the analysis path. The results showed that event significantly influence destination image and customer experience. Event and destination image not significantly influence on revisit intention, while the customer experience significantly influence on revisit intention. Customer experience serves as a variable that mediates the effect of the event to revisit intention.